Selective Degradation of Target Proteins by Chimeric Small-Molecular Drugs, PROTACs and SNIPERs - Minoru Ishikawa; Shusuke Tomoshige; Yosuke Demizu; Mikihiko Naito (MDPI AG, 2020)
New therapeutic modalities are needed to address the problem of pathological but undruggable proteins. One possible approach is the induction of protein degradation by chimeric drugs composed of a ubiquitin ligase (E3) ligand coupled to a ligand for the target protein. This article reviews chimeric drugs that decrease the level of specific proteins such as proteolysis targeting chimeric molecules (PROTACs) and specific and nongenetic inhibitor of apoptosis protein (IAP)-dependent protein erasers (SNIPERs), which target proteins for proteasome-mediated degradation. We cover strategies for increasing the degradation activity induced by small molecules, and their scope for application to undruggable proteins.